2009
DOI: 10.1152/jn.90828.2008
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuronal Innervation of Single Muscle Fibers in Cat Eye Muscle: Inferior Oblique

Abstract: Dimitrova DM, Allman BL, Shall MS, Goldberg SJ. Polyneuronal innervation of single muscle fibers in cat eye muscle: inferior oblique. J Neurophysiol 101: 2815-2821, 2009. First published March 18, 2009 doi:10.1152/jn.90828.2008. Single muscle fibers with multiple axonal endplates (multiply innervated fibers) are normally present in adult extraocular muscles (EOMs), while most other mammalian skeletal muscles contain fibers with a single myoneural junction. Recent findings by others led us to investigate for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…En grappe endplates are scattered longitudinally along a single muscle fiber, suggesting that many en grappe‐type junctions along a single muscle fiber are innervated by the same motor neuron. Moreover, unlike en grappe‐type junctions in other vertebrate muscles (Wilkinson and Lichtman, 1985; Lichtman et al, 1985), a lack of unoccupied AChR‐rich regions of the muscle membrane suggested that EOM en grappe‐type junctional sites are innervated by a single nerve terminal (Bach‐y‐Rita and Lennerstrand, 1975; but see Dimitrova et al, 2009). Unexpectedly, analysis of thy1:yfp‐lineH mice also demonstrated that some en grappe and en plaque NMJs were contacted by the same motor axon (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…En grappe endplates are scattered longitudinally along a single muscle fiber, suggesting that many en grappe‐type junctions along a single muscle fiber are innervated by the same motor neuron. Moreover, unlike en grappe‐type junctions in other vertebrate muscles (Wilkinson and Lichtman, 1985; Lichtman et al, 1985), a lack of unoccupied AChR‐rich regions of the muscle membrane suggested that EOM en grappe‐type junctional sites are innervated by a single nerve terminal (Bach‐y‐Rita and Lennerstrand, 1975; but see Dimitrova et al, 2009). Unexpectedly, analysis of thy1:yfp‐lineH mice also demonstrated that some en grappe and en plaque NMJs were contacted by the same motor axon (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…30 Electrophysiological data elegantly show that the sum of twitch and tetanic tensions in response to individual nerve branch stimulation is greater than that when the whole EOM nerve is simultaneously stimulated, indicating the presence of polyneuronal innervation. 27,28 In addition, by using silver teasing and/or acetylcholinesterase staining method, Dietert 5 and Oda 20 demonstrate multiterminal endplates that are innervated by several different motor axons, indicating the presence of polyneuronal innervation also in human EOMs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of neighboring en plaque endings with distinct AChR subunit composition on a given myofiber favors the possibility of polyneuronal innervation. The presence of polyneuronal innervation has been recognized electrophysiologically in the EOMs of mammals, including cat, [24][25][26][27][28] monkey, 26,29 and rat. 30 Electrophysiological data elegantly show that the sum of twitch and tetanic tensions in response to individual nerve branch stimulation is greater than that when the whole EOM nerve is simultaneously stimulated, indicating the presence of polyneuronal innervation.…”
Section: Discussionmentioning
confidence: 99%
“…This peculiar fiber array is possibly linked to multifocal innervation of the CM, with multiple end plates per single fiber [1]. Multi-innervation, as observed in EOMs [22] and laryngeal muscles [30], is likely to be related with the specific function of CM in the cremasteric reflex, allowing a subtle modulation of contractile parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent classifications individuate 11 MyHC isoforms in mammalian skeletal muscles, encompassing “classic” as well as “atypical” heavy chains, restricted to highly specialized muscular districts, such as extrinsic ocular muscles (EOMs) and jaw and laryngeal muscles [21]. These striated muscles share with the CM a nonsomitic embryological origin and peculiar morphological/functional features: multiple innervation with multiple plate ends [22, 23] and distinctive expression of MyHCs [24].…”
Section: Introductionmentioning
confidence: 99%